HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI DAN SANITASI MAKANAN PADA BAYI USIA KURANG DARI 6 BULAN DENGAN KEJADIAN DIARE - Wilda Wahyuni Siregar; Nita Triana Saragih; Supran Hidayat Sihotang; Novita Br Ginting Munthe; Dwi Handayani; Nikmah Jalilah Ritonga (JURNAL ILMIAH DHDT - KEBIDANAN, 2019)
Diarrhe is a disorder defection which be marked more than 3 times in a day with consistency of liquid, could accompany blood and mucus. This research have a aim to know the relation giving companio the food and the food sanitation to the baby by the age 0-6 in a month that happen in diarrhe, the location is Puskesmas Saribudolok, the area is center of Silimakuta and Simalungun district at 2018 year. This research is used to analytic observation with alignment (cross-sectional) the research of population is 179 respondes and the research sample as much as 89 respondes and used the formula lemeshow by taking the sample of consecutive sam. The data analysics by chi-square, the result of the research analysis to give companio the food is not good (84,3%). Giving the frequency mp-asi is not good (79,8%) and the method processing the food is not fulfill the requirment (87.6%), The way to keep the food is not fulfill yet the requirment (74,2%), The step to presentation the food is not fulfil yet the requirment (73.0%) ,The way using the eguiment/things the food is not fulfill yet the requirement (59.6%). Base on the result of bivariate analysis that kinds of companio the food, giving a frequency, the way to keep the food, the way to keep the equipments for food there is a relation with diarhe. And the way to process, presentation there is nothing the relation with have been happen of diarrhe. Base on the result of multivariate analysis, had known that the food sanitation thats a step to keep a food overall persentage storage (78.7%). Suggestions can be given to the community, for the next researcher and in the educational institution.